Beginning of the Basic Biomedical Sciences teaching at the Cienfuegos Medical Sciences Faculty. Development of Histology from 1982 to 1994 - José Emilio Caballero González; Martha del Carmen Acuna Caballero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
The teaching of basic biomedical sciences at the Cienfuegos University of Medical Sciences had its beginnings in 1982 with the opening of the first year of the medical career at the Medical Sciences Faculty of that southern province, initially dependent, since the methodological point of view, from the Villa Clara Medical Sciences Higher Institute. The directors, professors and technicians who began teaching with the first Carlos J. Finlay Medical Sciences detachment are mentioned in this research, the result of the Commander in Chief Fidel Castro Ruz' thought to universalize the teaching of medical sciences throughout the country. As the forty years of this teaching event in the Cienfuegos province were completed in 2022, this research serves as acknowledgement to the basic biomedical sciences teaching initiators in this province.